Neutrino Flavor Mixing with Approximate μ - τ Symmetry Within the Low-Scale Minimal Linear Seesaw Model - Matute-Carvajal, E (World Scientific, 2022)
Neutrino flavor mixing is explained within the recently proposed low-scale minimal linear seesaw model of neutrino mass generation, a variant of the standard linear seesaw led by a Dirac pair of extra sterile neutrinos which is odd under a discrete Z2 symmetry and has a mass at or below the GeV scale. The tri-bimaximal mixing and its deviations are derived straightforwardly on the basis of the symmetry between μ and τ flavors, without introducing non-abelian discrete flavor symmetries in the first place. © 2022 World Scientific Publishing Company.